Spectral analysis on optimizing X-ray tubes operating parameters and performance for non-destructive material quality analysis - Tarvonen, Jenna (2020)
This Master's Thesis was made in cooperation with the University of Jyväskylä and Stresstech Oy. The purpose of this work is to compare the X-ray tubes from two different manufacturers (TruFocus and MRX), to obtain information about the properties and function of tubes and changes in spectra when measuring with different acceleration voltages and currents. The goal is to get results with which to optimize the X- ray diffraction measurements in laboratory work. For this reason, I will also briefly present the diffraction phenomenon and intensity calculations used to analyze the diffraction spectrum in some of the XRD measurements.